Asia's food security in trouble? - Donnellon-May, Genevieve (2022)
The impact of the Ukraine-Russia conflict on food security in many countries demonstrates how inter-linked the global food system has become. Ripple effects from reduced wheat and fertiliser exports are already causing wheat shortages in the Middle East and fertiliser shortages elsewhere. However, the crisis also offers other major agricultural exporting countries opportunities.